A Preliminary Study on Determinats of Information Technology Acceptance Among Academicians in Libya - Maitieg, Ibrahim Ahmed (2010)
The aim of this study is to examine the determinants of information technology acceptance. This study is conducted in a University setting i.e. The Seventh October University Misurata in Libya. This study is conducted using a sample of 154 respondents and a survey type of study was used hence questionnaires were distributed to the respondents. The subsequent result after the analysis shows that all the independent variables i.e. perceived ease of use, perceived usefulness and trust are significantly related to information technology acceptance. A multiple regression was also conducted to see the contribution of each independent variable and the dependent variable. Discussions, recommendations and conclusions were also highlighted